The Effect of the Application of Food Exercise Emotion Smoking Alcohol Cessation and Social Support to Reduce the Risk of Diabetes and Hypertension among New Risk Groups - Tassana-iem, Sasiwan; กลยณี, สำรวย (Ratchaphruek Journal, 2019)
Abstract This study is quasi-experimental research aimed to test the effects of the application of food, exercise, emotion, smoking, alcohol cessation, and social support to reduce the risk of diabetes and hypertension. 100 of sample were a new risk people at Ban Na Kham Sub-district, Sakon Nakhon province. The research instruments were the program. The data were analyzed by descriptive statistic and compare the differences before and after the experiment with Paired - sample t-test. The result found that after the experiment, the sample with fasting blood sugar levels, blood pressure levels, triglyceride, body mass index and waist circumference decreased less than before with statistically significant at the level of 0.05 (p-value = <0.001, 0.009, <0.001, <0.001, <0.001, respectively). The results of this study were a guideline for reducing the risk of diabetes and hypertension in new risk groups. Relevant agencies can be used as a guideline for operations in groups that are similar to samples in order to reduce the rate of patients with diabetes and high blood pressure.